Effects of interaction of Meloidogyne incognita, Alternaria dauci and Rhizoctonia solani on the growth, chlorophyll, carotenoid and proline contents of carrot in three types of soil. (19th May 2019) - Ahmad, Lukman; Siddiqui, Zaki A.; Abd_Allah, Elsayed F.
ABSTRACT: Disease complex of carrot ( Daucus carota L.) involving root knot nematode Meloidogyne incognita and two fungi Alternaria dauci and Rhizoctonia solani were studied in three soil types. More plant growth, chlorophyll, carotenoid and proline contents were found in carrot grown in fly ash mix soil than plants grown in sand mix soil and loamy soil. Inoculation of M. incognita, R. solani, and A. dauci reduced plant growth, chlorophyll and carotenoid but increased proline contents. Inoculation of M. incognita 20 days prior to a fungal pathogen caused a greater reduction in plant growth, chlorophyll and carotenoid than fungal pathogen was inoculated prior. Inoculation of A. dauci prior to R. solani or vice versa had a similar effect on plant growth, chlorophyll, and carotenoid. Nematode multiplication and galling was higher in plants grown in sand mix soil followed by loamy soil and fly ash mix soil. Both fungi had adverse effects on galling and nematode multiplication. Blight disease index caused by A. dauci was 3 and crown rot index by R. solani was also recorded 3. These disease indices were 5 when pathogens were inoculated in combinations.